A critical study of methods for the determination of zinc in soils and plant materials - Eve, Desmond John (Rhodes University, Faculty of Science, Department of Chemistry, 1955)
Although it is only fairly recently that the importance of trace elements in plant nutrition has been established, enormous advances have been made in this field of research and numerous publications of considerable scientific and economic importance, dealing with the subject, have appeared. The physiological functions of zinc in promoting plant growth have not all been satisfactorily identified as yet. There are indications, however, that zinc acts as a catalyst or regulator in plant metabolism. It appears too, that the element plays some role in chlorophyll formation. Zinc deficiency is associated with leaf chlorosis and a general collapse of v ital processes. The analysis of leaves and soils has become an essential part of the study of the nutritional diseases of plants and it is imperative that accurate and reliable methods of analysis should be available. Intro. p. 1.
Keywords: Soils -- Zinc content; Soils -- Analysis; Plants -- Analysis